RELIGIUSITAS DAN KEBAHAGIAAN RELAWAN BENCANA - Nuryanti, Sofia; Akhrani, Lusy Asa (JURNAL TALENTA PSIKOLOGI, 2021)
The disaster that occurs does not rule out the possibility of causing casualties. Every disaster event requires the assistance of volunteers in assisting post-disaster management. This study examines the happiness of disaster volunteers in terms of religiosity. A quantitative approach is used in this study to determine the role of empathy on the happiness of disaster volunteers using linear regression analysis. Using accidental sampling, as many as 135 disaster volunteers were at least 18 years old and had helped the disaster evacuation process. The measuring instrument that will be used to measure the religiosity ability of disaster volunteers uses the religiosity scale using the Glock & Stark theory (1968) and the Oxford Happiness Questionnaires-Short Form (OHQ-S) scale which is used to measure the level of happiness. The results of the regression analysis show that empathy can significantly predict happiness in disaster volunteers. The regression results also show that the role of religiosity contributes 19.6% of the variance in the happiness of disaster volunteers.